Water relations and yield characteristics of mungbean as influenced by foliar application of gibberellic acid (GA3) - Islam, Mohammad Sohidul; Hasan, Md. Kamrul; Islam, Md. Rafiqul; Chowdhury, Md. Kaium; Pramanik, Moaz Hosen; Iqbal, Muhammad Aamir; Rajendran, Karthika; Iqbal, Rashid; Soufan, Walid; Kamran, Muhammad; Liyun, Liu; El Sabagh, Ayman (Frontiers in Ecology and Evolution, 2023)
Optimizing the dose and foliar application frequency of growth regulators such as gibberellic acid (GA3) may play an important role in ensuring food security under changing climate scenarios by boosting grain yield of food legumes such as mungbean. A trial was conducted to evaluate the growth promoting effect of foliage applied gibberellic acid (GA3) at various spraying frequencies for mungbean crop. The employed treatments included four gibberellic acid levels (0, 100, 200, and 300 ppm) and two application frequencies (single spray at 30 days after sowing DAS, and two sprays at 30 and 40 DAS). Water relations, yield contributing characteristics and mungbean grain yield were among the response variables investigated. The research findings revealed that GA3 (200 ppm applied twice at pre-flowering and post-flowering stages) significantly improved the water relations, morphological and yield attributes of mungbean. This treatment combination remained unmatched by producing the highest relative water content in the stem (85.52), water retention capacity in the stem (17.24), and water uptake capacity in the stem and leaf (2.35). Furthermore, the same treatment combination resulted in the maximum plant height (50.04 cm), pods per plant (11.07), pod length (6.62 cm), grains number per pod (11.00), 100-grains weight (3.78 g), grain yield per plant (4.57 g), and a minimum water saturation deficit. Thus, GA3 foliage application at 200 ppm at 30 and 60 DAS has the potential to stimulate growth and increase the yield attributes and grain yield of mungbean. However, additional in-depth field trials with various doses of GA3 sprayed at a higher frequency may be required before recommending GA3 for general adoption to mungbean growers.